2022
DOI: 10.3390/su14063476
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Monitoring Costs Charged for Auditing Fair Value Model: Evidence from Jordanian Finance Industry

Abstract: This article inspects the likely outcome of using the fair value (FV) concept on audit firms’ anomalous audit fees. The research performs fixed effects regression to evaluate the given hypotheses using data gathered by hand from 105 Jordanian publicly traded enterprises between 2005 and 2018. The study reveals that FV proxies have a favorable and substantial effect on the atypical audit fees paid by Jordanian enterprises. The findings are more evident for businesses with a higher percentage of subjective FVs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…(2020) reported that audit firms are now conducting virtual audits using expensive and complex cutting-edge technology to obtain financial evidence and provide expertise for more adaptable client communications. Alharasis et al (2022) stated that auditors were expected to spend a longer period on their work and charge greater costs during financial crises. According to research by Harjoto and Laksmana (2022), global audit costs and latency rose as a result of COVID-19 lockdowns and hospital limitations.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…(2020) reported that audit firms are now conducting virtual audits using expensive and complex cutting-edge technology to obtain financial evidence and provide expertise for more adaptable client communications. Alharasis et al (2022) stated that auditors were expected to spend a longer period on their work and charge greater costs during financial crises. According to research by Harjoto and Laksmana (2022), global audit costs and latency rose as a result of COVID-19 lockdowns and hospital limitations.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Concerns for the auditing profession include charging reasonable rates, using competent people and providing valid audit opinions. Researchers have hypothesized that the financial performance, risk and liquidity of customers are positively correlated with economic conditions (Alharasis et al , 2022; Albitar et al , 2021), which, in turn, affects audit fees. Companies can default on lending agreements during economic downturns.…”
Section: Theoretical Background and The Development Of Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of Jordan's 300 audit firms are small. Big 4 auditing companies operate there (Alharasis et al, 2022b). Jordan's JACPA certifies accountants (Abdullatif and Al-Rahahleh, 2020).…”
Section: Institutional Background: the Rationale Behind The Contextmentioning
confidence: 99%